The thermal limits to life on Earth. Issue 2 (14th January 2014) - Clarke, Andrew
Abstract: Living organisms on Earth are characterized by three necessary features: a set of internal instructions encoded in DNA (software), a suite of proteins and associated macromolecules providing a boundary and internal structure (hardware), and a flux of energy. In addition, they replicate themselves through reproduction, a process that renders evolutionary change inevitable in a resource-limited world. Temperature has a profound effect on all of these features, and yet life is sufficiently adaptable to be found almost everywhere water is liquid. The thermal limits to survival are well documented for many types of organisms, but the thermal limits to completion of the life cycle are much more difficult to establish, especially for organisms that inhabit thermally variable environments. Current data suggest that the thermal limits to completion of the life cycle differ between the three major domains of life, bacteria, archaea and eukaryotes. At the very highest temperatures only archaea are found with the current high-temperature limit for growth being 122 °C. Bacteria can grow up to 100 °C, but no eukaryote appears to be able to complete its life cycle above ∼60 °C and most not above 40 °C. The lower thermal limit for growth in bacteria, archaea, unicellular eukaryotes where ice is present appears to be set by vitrification of the cell interior, and lies at ∼−20 °C. Lichens appear to be able to grow down to ∼−10 °C. Higher plants and invertebrates living at high latitudes can survive down to ∼−70 °C, but the lower limit for completion of the life cycle in multicellular organisms appears to be ∼−2 °C.